The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-02138-w
|View full text |Cite
|
Sign up to set email alerts
|

Determination of probability of causative pathogen in infectious keratitis using deep learning algorithm of slit-lamp images

Abstract: Corneal opacities are important causes of blindness, and their major etiology is infectious keratitis. Slit-lamp examinations are commonly used to determine the causative pathogen; however, their diagnostic accuracy is low even for experienced ophthalmologists. To characterize the “face” of an infected cornea, we have adapted a deep learning architecture used for facial recognition and applied it to determine a probability score for a specific pathogen causing keratitis. To record the diverse features and miti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 78 publications
(27 reference statements)
0
28
0
1
Order By: Relevance
“…54 In areas or circumstances where patients are unable to access ophthalmic care, the ability to diagnose and assess microbial keratitis through artificial intelligence using external eye photos, such as could be taken with a mobile phone, may allow for appropriate therapy to be commenced without delay. 2,5,[54][55][56] 3 | HERPES SIMPLEX KERATITIS…”
Section: Deep Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…54 In areas or circumstances where patients are unable to access ophthalmic care, the ability to diagnose and assess microbial keratitis through artificial intelligence using external eye photos, such as could be taken with a mobile phone, may allow for appropriate therapy to be commenced without delay. 2,5,[54][55][56] 3 | HERPES SIMPLEX KERATITIS…”
Section: Deep Learningmentioning
confidence: 99%
“…Investigators using external eye photographs to assess deep learning frameworks in BK have reported that the diagnostic accuracy of different models ranged from 69% to 72%; comparable to ophthalmologists (66% to 74%) 54 . In areas or circumstances where patients are unable to access ophthalmic care, the ability to diagnose and assess microbial keratitis through artificial intelligence using external eye photos, such as could be taken with a mobile phone, may allow for appropriate therapy to be commenced without delay 2,5,54–56 …”
Section: Bacterial Keratitismentioning
confidence: 99%
See 1 more Smart Citation
“…Various reports have described the use of artificial intelligence deep learning to identify the presence of infectious keratitis, or determine type of infection based on imaging [45][46][47][48][49][50][51].…”
Section: Diagnosticsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Within the realm of ophthalmology, DL research previously focussed mainly on various posterior segment diseases (e.g., age-related macular degeneration, diabetic retinopathy, and glaucoma) and demonstrated comparable, if not better, diagnostic accuracy compared to healthcare professionals. 22,23,[29][30][31] Although several recent studies have demonstrated the potential of DL in assisting the diagnosis of IK and distinguishing IK from other ocular diseases, [32][33][34][35] the diagnostic accuracy of these DL models remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%